(untitled) (Journal of Universal Excellence, 2026)
Research Question (RQ): What are the advantages and disadvantages of teamwork at distance? Purpose: To explore the advantages and disadvantages of teamwork at a distance and to find the reasons for successful or unsuccessful work at a distance. Method: With the help of an integrative review of the literature or already done research in this field and with the collection of data, we investigated the advantages and disadvantages of teamwork at a distance. To obtain data, we used a qualitative method, a compilation method with which we summarized the results of other authors on this topic, a comparative method for comparing the advantages and disadvantages of teamwork at a distance and a deductive method with which we infer individual cases in general. Results: The results of all surveys do not differ significantly, as the advantages and disadvantages of teamwork at a distance of employees depend on similar parameters: working hours, age, position in the company, infrastructure, possibilities of combining work and family. Organization: The impact on the organization is strong as it allows the organization to achieve better employee productivity, they can have a flexible work schedule, the organization does not have high costs with physical offices and with the cost of transporting employees to work. It is also important that organizations are aware of the importance of the benefits of teleworking and encourage productivity, innovation, and that the leader rewards them accordingly. Society: Theoretical part starting points guide society to the use of telework and teamwork, as more people together can do much more, improve, innovate. Teleworking has a positive effect on employees. Originality: The originality of the research is reflected in the breakdown of the advantages and disadvantages of teamwork at a distance. The topic focused on highlighting the benefits of teamwork at a distance, which greatly contributes to the development of the company. Limitations/Future Research: To get a broader view of the advantages and disadvantages of teamwork at a distance, more literature would need to be examined. For further research, we should explore the various costs that threaten companies in terms of introducing telework and ways to help companies and employees work remotely in a team.